2016
DOI: 10.3390/catal6050067
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression and Characterization of a Novel Fructosyltransferase from Aspergillus oryzae ZZ-01 for the Synthesis of Sucrose 6-Acetate

Abstract: A 1521 bp gene encoding for a novel fructosyltransferase from Aspergillus oryzae ZZ-01 (AoFT) has been amplified by RACE and TAIL PCR, and functionally overexpressed in Escherichia coli BL 21-CodonPlus (DE3)-RIL. The recombinant A. oryzae ZZ-01 fructosyltransferases (r-AoFT) was purified to homogeneity after Ni-NTA affinity and Superdex-200 gel filtration chromatography. SDS-PAGE analysis of the purified r-AoFT revealed a single protein band with an apparent molecular mass of 60.0 kDa. The r-AoFT enzyme exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Two FTases, namely AcFT1 and AcFT2, from A. aculeatus were 70 kDa and 100 kDa proteins (Virgen‐Ortíz et al., 2016). Molecular weight of A. oryzae FTase was observed to be 50 kDa (T. Wei et al., 2016). Recently, A. oryzae S719 FTase (95 kDa) has been purified using Sephacryl S‐200 HR and DEAE‐Sepharose matrices (Han et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two FTases, namely AcFT1 and AcFT2, from A. aculeatus were 70 kDa and 100 kDa proteins (Virgen‐Ortíz et al., 2016). Molecular weight of A. oryzae FTase was observed to be 50 kDa (T. Wei et al., 2016). Recently, A. oryzae S719 FTase (95 kDa) has been purified using Sephacryl S‐200 HR and DEAE‐Sepharose matrices (Han et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Deglycosylated (Endo‐H treated) extracellular recombinant Aureobasidium melanogenum 11−1 FTase purified using nickel‐NTA column had molecular weight of 82.4 kDa (Aung et al., 2019). Some other reports also suggested that most of the fungal FTases are reported to have molecular weights in the range of 50–90 kDa (Aung et al., 2019; T. Wei et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The 3D model structure of A. oryzae ZZ‐01 fructosyltransferase was modeled based on the crystal structure of Schwanniomyces occidentalis fructofuranosidase (PDB: 3u75.1A). The model also includes two domains, i.e., an N ‐terminal five‐blade β ‐propeller fold harboring the active site, and a C ‐terminal β ‐sandwich domain 69.…”
Section: Characteristics Of Fructosyltransferasesmentioning
confidence: 99%
“…Additionally, metal ions play an important role in the folding of proteins 13. Structures of enzymes can be altered by metal ions, which can lead to denaturation 69. Fructosyltransferase can be also activated or inhibited by certain metal ions.…”
Section: Characteristics Of Fructosyltransferasesmentioning
confidence: 99%
“…Any further increase or decrease in the HSP concentration resulted in a decrease in 2,5-DHP production. Thus, increasing the HSP concentration (from 0.25 to 1 mM) facilitated contact between the enzyme and the substrate in the reaction system [27]. The Michaelis-Menten equation was applied for catalytic kinetic analysis.…”
Section: Effect Of Enzyme and Substrate Concentration On 25-dhp Prodmentioning
confidence: 99%